1997
DOI: 10.2307/2445815
|View full text |Cite
|
Sign up to set email alerts
|

Desiccation‐time limits of photosynthetic recovery in Equisetum hyemale (Equisetaceae) spores

Abstract: The chlorophyllous spores of Equisetum survive desiccation, yet cannot tolerate this quiescent state for more than ~2 wk. The hypothesis that spore viability of Equisetum hyemale L. is limited by inhibition of photosynthetic recovery was tested using chlorophyll a fluorescence and oxygen-exchange analyses. Experimental spores were desiccated at 2% relative humidity and 25C for time periods of 24 h, 1 wk, and 2 wk, and then rehydrated at 200 mmol photons/m2s (PAR) and 25C for up to 24 h. Spores desiccated for 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 50 publications
0
20
0
Order By: Relevance
“…Desiccation-tolerant spores have been reported from pteridophytes (e.g. 33 fern species with nonchlorophyllous spores and five fern species with chlorophyllous spores; Pence 2000) and from the distantly related sphenophyte Equisetum hyemale L. (spore PDT approximately -525 MPa, Lebkuecher 1997). Desiccationtolerant spores are common in the mosses dispersed across oceans (Van Zanten 1978).…”
Section: Desiccation-tolerance In Other Photosynthetic Organismsmentioning
confidence: 99%
“…Desiccation-tolerant spores have been reported from pteridophytes (e.g. 33 fern species with nonchlorophyllous spores and five fern species with chlorophyllous spores; Pence 2000) and from the distantly related sphenophyte Equisetum hyemale L. (spore PDT approximately -525 MPa, Lebkuecher 1997). Desiccationtolerant spores are common in the mosses dispersed across oceans (Van Zanten 1978).…”
Section: Desiccation-tolerance In Other Photosynthetic Organismsmentioning
confidence: 99%
“…The onset for lipid crystallization is indicated by a horizontal dashed line. The shaded area is the temperature range where lipid melting transitions were detected to speculate that the inability to recover from losses of photosystem II (PSII) core function upon rehydration, as time in the dry state progressed in the green spores of E. hyemale (Lebkuecher 1997), could be related to an accumulation of oxidative damage in dry spores. Light is absorbed by the pigments of the photosynthetic apparatus of such spores when they are stored dry, and it is known that when water is absent, parts of PSII threaten to oxidise components of the photosynthetic apparatus, particularly when the antioxidant machinery is depleted (Kranner et al 2002(Kranner et al , 2008Illing et al 2005;Heber et al 2006;Farrant 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Light is absorbed by the pigments of the photosynthetic apparatus of such spores when they are stored dry, and it is known that when water is absent, parts of PSII threaten to oxidise components of the photosynthetic apparatus, particularly when the antioxidant machinery is depleted (Kranner et al 2002(Kranner et al , 2008Illing et al 2005;Heber et al 2006;Farrant 2007). An improved understanding of the ageing mechanisms of green spores during dry storage could therefore benefit from an investigation of the activity of specific (particularly enzymic) antioxidants in these spore in relation to the loss of function of the photosystems (Lebkuecher 1997;Kranner and Birtic 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For comparison, our study revealed that the spore germination of O. regalis (99.9 %) was not affected even by desiccation to 4.6 % MC (eRH = 18.5 %). According to Lebkuecher (1997) the chlorophyllous spores of Equisetum hyemale can be desiccated almost completely following storage at 25°C and 2 % RH. Ninety percent of the spores survived that extreme, however, not longer than 1-weeklong, desiccation to 4 % relative water content.…”
Section: Discussion Desiccation Tolerance Of Green Sporesmentioning
confidence: 99%